Algorithm proposal for hair transplantation in fibrosing alopecia pattern distributidon. (7th June 2022) - Gómez‐Zubiaur, Alba; Valenzuela, Cristian; Andrés‐Lencina, Juan José; Rodríguez‐Villa, Ana; Ricart, Jose MarÍa
Abstract: Fibrosing alopecia pattern distribution (FAPD) is a recently described disease, wherein the clinical, trichoscopic, and histologic characteristics of non‐scarring alopecia, such as androgenic alopecia, and lichenoid inflammatory cicatricial alopecia are reported. The lack of uniformity in the diagnostic criteria can result in FAPD overdiagnosis. The characteristic findings of loss of follicular openings on trichoscopy and fibrosis on histopathology are crucial, as they are necessary to diagnose cicatricial inflammatory lichenoid alopecias. Â Hair transplantation in FAPD can be controversial. The scarce publications in this realm do not reach a clear consensus in favor or against the surgical approach. Thus, the presence of histological lichenoid inflammatory infiltrates could make this therapeutic option less suitable. There have been few reports on hair transplantation in other lymphocytic lichenoid inflammatory alopecias, such as lichen planus pilaris (LPP) and frontal fibrosing alopecia (FFA) Â Based on those data, an algorithm for the indication of hair transplantation in FAPD is proposed. The algorithm optimizes the results of the treatment and achieves the greatest coverage of the alopecic area.